2018
DOI: 10.1002/fut.21966
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric spot‐futures price adjustments in grain markets

Abstract: Recent volatility in food prices in the grain market has generated much interest among agricultural market participants. This study examines the nonlinear dynamic relationship between spot and futures prices in grain markets. The empirical results provide strong evidence of price asymmetries. The corn spot price adjusts faster to futures price increases than futures price decreases, whereas the soybean spot price adjusts faster to futures price decreases than futures price increases. Although this asymmetric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 68 publications
3
12
0
Order By: Relevance
“…Hence, it is generally believed that futures markets play a leading role (or a relatively more important role) in the price discovery process than cash markets. Many empirical studies generally confirm that futures prices tend to lead cash prices on agricultural commodity markets (Adämmer & Bohl, 2018; Carter & Mohapatra, 2008; Wu et al, 2018; Yang et al, 2001) in the United States, Europe, and other developed countries. Nevertheless, recent evidence suggests that cash markets can generally be as important as futures markets in the price discovery of a major U.S. agricultural commodity (X. Xu, 2018), and that the opposite may even exist on other financial (e.g., currency) markets (e.g., Cabrera et al, 2009; Chen & Gau, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Hence, it is generally believed that futures markets play a leading role (or a relatively more important role) in the price discovery process than cash markets. Many empirical studies generally confirm that futures prices tend to lead cash prices on agricultural commodity markets (Adämmer & Bohl, 2018; Carter & Mohapatra, 2008; Wu et al, 2018; Yang et al, 2001) in the United States, Europe, and other developed countries. Nevertheless, recent evidence suggests that cash markets can generally be as important as futures markets in the price discovery of a major U.S. agricultural commodity (X. Xu, 2018), and that the opposite may even exist on other financial (e.g., currency) markets (e.g., Cabrera et al, 2009; Chen & Gau, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…The presence of APT has been confirmed for the US and Canadian grain markets, implying the most profitable opportunities for traders when the basis is narrowing (Chang et al 2012). Similarly, Wu et al (2018), confirmed the presence of negative APT between the Chicago futures market and the Ontario spot market for soybean while the corn markets showed positive APT. Their finding suggests that operators of assorted commodities must resort to different trading strategies in response to shock.…”
mentioning
confidence: 70%
“…(4) (5) where: Δy t ; Δx t -lagged log differences of spot (futures) and futures (spot) prices from the time interval (i) 1 to l (the number of selected lags); α 0 -intercept terms; γ 1 -coefficient of the lagged differenced futures (spot) representing the short-run transmission; and γ 2autoregressive coefficient of the spot (futures) prices; ECT -error correction term; γ 3 , γ 4 -adjustment coef-ficients calculated according to the Heaviside indicator (I t ) setting; τ = 0 (Wu et al 2018).…”
Section: This Impliesmentioning
confidence: 99%
See 1 more Smart Citation
“…cotton futures had mostly stable leading effect on cotton spot and forward markets during a period where policy interventions were particularly dramatic. Wu et al ( 2018 ) researched the asymmetric price adjustment between spot and futures prices for corn and soybeans markets, utilizing threshold cointegration models. According to their findings, the local spot prices of corn and soybeans adjust to restore long‐run equilibrium, respective to futures market at the CME.…”
Section: Brief Literature Review and Related Studiesmentioning
confidence: 99%